Corporate income tax and wages: a meta-regression analysis - Knaisch, Jonas,Pöschel, Carla (Arbeitskreis Quantitative Steuerlehre, 2021)
In this paper we apply meta-regression analysis to quantitatively review the growing empirical tax incidence literature that indicates a substantial burden of the corporate income tax falling on employees. While most studies report large negative wage elasticities to corporate taxes, our findings suggest that estimates with positive values are published less often than they should. After accounting for publication bias, we estimate an average wage elasticity to corporate taxes of -0.016. Moreover, methodological aspects (data coverage and temporal focus) drive the heterogeneity among estimates. Our consensus estimates suggest a long-term wage elasticity to corporate taxes between -0.105 and -0.141, depending on the underlying CIT burden variable and the type of data used.
10419/231988
Keywords: Graue Literatur; Tax incidence; wages; corporate income tax; wage elasticity to taxes; meta-regression analysis